Multiculturalismo e Interculturalidade no Direito à Educação Superior dos Povos Indígenas: Um Olhar para as Experiências da Universidade Federal de Mato Grosso do Sul - Felipe Augusto Rondon de Oliveira (2024)
The indigenous peoples in Brazil, since the 16th century, have survived a context of decimation and multiple genocides, attempts at integration and cultural assimilation, and a complete absence of rights, reaching the current growing but insufficient framework of state protection. Nevertheless, Brazil has a population of over one million and six hundred thousand indigenous people, distributed among more than three hundred ethnicities. In analyzing any rights involving these native peoples, a perspective of respect for alterity must be adopted, questioning the Eurocentric idea that the habits and customs of one group are superior to those of others, in a context of multiculturalism, as a movement and precondition seeking to preserve, respect, and value their cultural differences, and of interculturality, as an interactive process of mutual learning, horizontal and synergistic between different cultures. In this context, it is pertinent to question the bases and the very meaning that education assumes in these communities, their contradictions and new possibilities, and to rethink the ways of addressing their aspirations, seeking to problematize and understand this present, and to plan the future, which is intended to be done through the analysis of two relevant governmental actions designed and executed by the Federal University of Mato Grosso do Sul, the Indigenous Intercultural Teaching Degree "Pantanal Peoples," whose scope is to train indigenous teachers, in an intercultural manner, for the final grades of elementary school and for high school, and the "Connected Villages" Project, instituted to establish connection to the worldwide computer network in indigenous communities of the region, especially considering the restrictions of the coronavirus pandemic, and the alternation of education models to distance and hybrid learning systems. This research aims to address the following problem: do public policies regarding higher education for Indigenous Peoples implemented by the Federal University of Mato Grosso do Sul respect multiculturalism and interculturality? Thus, the general objective of this study is to analyze the governmental actions called Indigenous Intercultural Teaching Degree "Pantanal Peoples" and "Connected Villages" Project to understand the effective presence, respect, and role of multiculturalism and interculturality in the pursuit of the realization of the fundamental right to higher education for these peoples. The specific objectives are to analyze the right to education of Indigenous Peoples in the global and inter-American human rights systems, as well as in the Brazilian internal legal system, and to understand, in this context, the phenomena of multiculturalism and interculturality, and then to situate and define public policies from the "Law and Public Policies" (LPP) approach, presenting the methodological tool of the "Framework of Public Policy Reference," which will serve as a basis for the intended case studies. Regarding the methodological approach, this study is characterized as a bibliographical and focal observation research, which will use the aforementioned approach and its methodological tool to analyze the mentioned governmental actions of the Federal University of Mato Grosso do Sul, of relevant social impact, which have contributed to transforming higher education for Indigenous Peoples in this state.